Trustworthy blockchain‐based medical Internet of thing for minimal invasive surgery training simulator. (4th August 2020) - Tai, Yonghang; Wang, Yinjia; Wang, Zhifeng; Li, Feiyan; Wei, Lei; Pan, Lei; Zhang, Jun; Shi, Junsheng
Summary: Realistic modeling of mechanical behavior of soft tissue has been recognized as an essential part for medical Internet of thing for minimal invasive surgery (MIS) training simulator. Therefore, the blockchain‐based constitutive model is crucial for mechanical response of soft tissue modeling. In this article, based on the Ogden second order model, a novel hyperplastic model was presented to describe the stress‐stretch relationship in the MIS training system. To validate this theoretical model, two experimental techniques (uniaxial compression and uniaxial tensile) were conducted to obtain data related to stress‐strain in the blockchain system, which plays an important role in investigating the mechanical behavior of soft tissue. Our results show that the new model has a satisfied coincidence of the experimental data than other existing models. Furthermore, the viscoelastic properties of soft tissue were investigated and a viscoelastic model based on three‐parameter was utilized to interpret the viscoelastic behavior of the soft tissue. The contributions of this article include several biomechanical tests that were performed to investigate the soft tissue hyperelastic and viscoelastic properties in the MIS system, and theoretical guidance for simulating soft tissue mechanical behavior in the blockchain‐based simulation system.